Observations on the Disposition of Hebrews - Lang, Friedrich Gustav (Novum Testamentum, 2019)
The disposition of Hebrews is analyzed in terms of literary structure and significant proportions. The discussion of differing proposals for the letter leads to an outline of five main parts. Two christological sections (1:1-2:18; 7:1-10:18) alternate with two hortatory ones calling to faith (3:1-6:20; 10:19-12:29), then follow general exhortations (13:1-21), finally an epistolary appendix (13:22-25). The stichos of 15 syllables is introduced as the ancient standard measure of Greek prose. Counting stichoi in Hebrews reveals remarkable proportions seemingly due to intentional disposing. The letter's first main part, for example, is half the size of the second one, and both together half the size of the whole. All results of the structural and stichometrical analysis are then condensed in a tabular outline.